Some 'R' points: Repression, repulsion, revelation and redemption in South Korean horror films. Issue 2 (1st October 2020) - Diffrient, David Scott
This article examines some of the formal properties, stylistic motifs and thematic preoccupations of classic and contemporary South Korean horror films. As a genre that has enormous box-office appeal and crossover potential for western audiences, horror might seem to be little more than a commercial platform for young filmmakers to exploit popular tastes and cash in on derivative stories offering scant insight into the social conditions faced by modern-day Koreans. However, even the most cliché-ridden, shock-filled slasher films and ghost tales reveal the often-contradictory cultural attitudes of a populace that, over the past three generations, has weathered literally divisive transformations at the national and ideological levels. As such, the genre deserves scrutiny as a repository of previously pent-up, suddenly unleashed libidinal energies, consumerist desires and historical traumas, as well as a barometer of public opinion about such issues as class warfare, gender inequality and sexual identity. Specifically, I explore some of the most salient features of Korean horror cinema, including filmmakers' tendency to adopt narrative analepsis ‐ typically rendered as flashbacks ‐ in the course of plotting out scenarios that, though far-fetched, are rooted in unsettled (and unsettling) real-world problems. Historical return, I argue, truly is a horrifying prospect, especially for anyone old enough to remember, or to have experienced firsthand, the brutality of a military dictatorship or an ongoing abuse of presidential power resulting in severe rights violations (e.g. the Park Chung-hee [1961‐79]) and Chun Doo-hwan [1980‐88] administrations). But historical return simply must be dramatized as part of the regurgitative 'purging' for which the genre has been singled out by theorists who recognize horror's socially productive function.